Shaping the microenvironment: evidence for the influence of a host galaxin on symbiont acquisition and maintenance in the squid‐vibrio symbiosis. (3rd June 2014) - Heath‐Heckman, Elizabeth A. C.; Gillette, Amani A.; Augustin, René; Gillette, Miles X.; Goldman, William E.; McFall‐Ngai, Margaret J.
Summary Most bacterial species make transitions between habitats, such as switching from free living to symbiotic niches. We provide evidence that a galaxin protein, EsGal1, of the squid Euprymna scolopes participates in both: (i) selection of the specific partner Vibrio fischeri from the bacterioplankton during symbiosis onset and, (ii) modulation of V. fischeri growth in symbiotic maintenance. We identified two galaxins in transcriptomic databases and showed by quantitative reverse‐transcriptase polymerase chain reaction that one (esgal1) was dominant in the light organ. Further, esgal1 expression was upregulated by symbiosis, a response that was partially achieved with exposure to symbiont cell‐envelope molecules. Confocal immunocytochemistry of juvenile animals localized EsGal1 to the apical surfaces of light‐organ epithelia and surrounding mucus, the environment in which V. fischeri cells aggregate before migration into the organ. Growth assays revealed that one repeat of EsGal1 arrested growth of Gram‐positive bacterial cells, which represent the cell type first 'winnowed' during initial selection of the symbiont. The EsGal1‐derived peptide also significantly decreased the growth rate of V. fischeri in culture. Further, when animals were exposed to an anti‐EsGal1 antibody, symbiont population growth was significantly increased. These data provide a window into how hosts select symbionts from a rich environment and govern their growth in symbiosis.